HUBUNGAN SOSIAL EKONOMI ANTARA PETANI SAWIT DENGAN TAUKE SAWIT DI DESA PETAI BARU KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Siti Aliyah; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Indonesia is a developing country, characterized by the development of cities in Indonesia in quick time. Agriculture is very important to people's lives in the continued existence of life in achieving a better life, but in meet the needs of all people can not reach it without the help of others. this study aimed to analyze the relationship between patron and palm farmers in the village of Petai baru of Singingi District, Kuantan Singingi with population of 1501 people and as many as 417 families in the village of Petai baru has 3 tatron and each patron have an accomplice as a customer permanent. The relationship between farmer with palm patron can be said as a patron-client relationship. Revenues were slightly farmer can not meet the needs of daily life so that the head of the family must come up with a debt to palm tatron, not only owe patron but owed others also done by farmer in order meet their needs even though most of the farmers oil has a second job sometimes it is also not sufficient for their lives. With the high rate of loan accounts payable will be undertaken by farmers to patron palm, farmers always have ties continued dependence. This makes tauke happy with farmer who always relies on patron, the farmers often owe the greater the benefits received by patron palm crop growers.Keywords: socio-economic relations, patron palm, palm far